STRATEGI GURU DALAM MENGELOLA PEMBELAJARAN ANAK AUTIS DI BIMBINGAN BELAJAR WIDYA WICARA KOTA SERANG - Latifah; Yahdinil Firda Nadirah (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to describe in depth the strategies used by teachers in managing the learning process of children with Autism Spectrum Disorder (ASD) at Bimbingan Belajar Widya Wicara. Using a descriptive qualitative approach through semi-structured interviews with the institution and direct observation of classroom activities, the findings show that teachers employ various adaptive strategies such as visual media, concrete and hands-on learning activities, positive reinforcement, individualized approaches, and attention-redirection techniques when children experience tantrums, difficulty focusing, or challenges in emotional regulation. A structured learning environment with minimal distractions, supported by the presence of two teachers in one session, helps create a sense of safety and enhances children’s engagement. Additionally, active communication and collaboration between teachers and parents strengthen the continuity of learning at home and support the monitoring of each child’s development. Overall, the study highlights that the learning strategies implemented at Widya Wicara are flexible, responsive, and child-centered, effectively supporting the academic, social, and emotional development of children with autism.